Embedded systems design - Heath, Steve (Newnes, 2003)
In this new edition the latest ARM processors and other hardware developments are fully covered along with new sections on Embedded Linux and the new freeware operating system eCOS. The hot topic of embedded systems and the internet is also introduced. In addition a fascinating new case study explores how embedded systems can be developed and experimented with using nothing more than a standard PC. * A practical introduction to the hottest topic in modern electronics design * Covers hardware, interfacing and programming in one book * New material on Embedded Linux for embedded internet systems
Includes index
Keywords: Systèmes enfouis (Informatique); Systèmes, Conception de; COMPUTERS / Hardware / Personal Computers / General; COMPUTERS / Hardware / Handheld Devices; COMPUTERS / Microprocessors; Embedded computer systems / Design and construction; Embedded systems; Ontwerpen; Embedded computer systems -- Design and construction; Eingebettetes System; Systementwurf